PERSPEKTIF AL-QUR’AN TENTANG MAHAR PERNIKAHAN DALAM MASYARAKAT TERBUKA - Masrokhin *, - - (Irtifaq, 2015)
This article discusses the variant of dowry in religious texts (Qur'an and Hadith). This research bibliographycal concluded that first the Qur'an never express with word mahar to the dowry, which connotes a transactional-materialistic, but rather use the word s}aduqat that leads to the philosophical significance of universality and restore meaning to the meaning that must be given a dowry by the male thus shifting the materialistic perception symbol of love. Second , an order to giving dowry is not a absolute command but the command is relative and tentative in the socio-cultural context that is constantly changing. So, looking at the concept of dowry from the perspective of the Qur'an affirms that the concept of al-Qur'an is true in any society. Keyword : bride-price, al-Qur’an perspectif, s}aduqat.